Asteroids and Ophiuroids Associated With Sponge Aggregations as a Key to Marine Habitats. A Comparative Analysis Between Avilés Canyons System and El Cachucho, Marine Protected Area - Manjón-Cabeza, Maria Eugenia; Ríos, Pilar; García-Guillén, Laura María; Macías-Ramírez, Aurora; Sánchez, Francisco; Rodríguez-Básalo, Augusto; Ibarrola, Teodoro P.; Cristobo, Javier (Frontiers in Marine Science, 2021)
This study analyzes composition of the taxocoenosis of brittle and sea stars associated with the sponge aggregations from Avilés Canyons System and Le Danois Bank. Diverse sampling methods were used as rock dredges and others for sedimentary bottoms. These banks are made up of sponge and coral species very appropriate substrate for the proliferation of benthic species, which create Vulnerable Marine Ecosystems, highly relevant for managing and conservation. Among these benthic species, echinoderms have a high interest due they are good habitats indicators. In total, 1261 specimens were collected (934 brittle star and 327 starfishes), which belong to 42 species (28 ophiuroids and 14 asteroids) from INDEMARES AVILÉS, ECOMARG and SponGES projects surveys. These are distributed among the four sponge aggregations (F: fields) that were previously defined according to the sponge records obtained (36 stations). These fields were defined and named based on 5 most occurrence sponge species: Aphrocallistes beatrix and Regadrella phoenix (F1: Avilés Canyon); Pheronema carpenteri (F2: Intraslope basin of Le Danois Bank) Asconema setubalense (F3: Le Danois Bank), Neoschrammeniella aff. bowerbankii (F4: Corbiro Canyon). The faunistical results have shown that Ophiactis abyssicola (55.55% ocurrence), Brisinga endecacnemos, Ophiolycus purpureus and Peltaster placenta (33.33%) are the most frequently species found at F1. Psilaster andromeda (80%) Pseudarchaster parelii (60%), Nymphaster arenatus (46.67%) at F2, F3: Ophiura carnea (71.43%) and Ophiacantha smitti (42.86%), and F4: Ophiacantha densa and Henricia caudani (100%). Echinoderms taxocoenosis seem to be composed of four different communities related to the presence of specialized species in the use of the resources that they can find there. In general, the abiotic factor which controls this structure is depth. This assemblage structure, favors the dissimilarity between the canyons and the bank, is not clear, since the deepest stations are located in the intraslope basin of the bank, therefore to use them a priori, could lead to misunderstandings Once the structure of the echinoderms taxocoenosis is known, we could compare the expected and obtained results to analyze the evidence which should prove the existence of any association between the echinoderms and sponges, results which allow us to refute the incongruous hypothesis.